An Action Error of Nursing Procedures: Types and Cause Factor Ners Profession Student - Uswatun Khasanah (Universitas Airlangga, 2012)
Introduction: An error could be danger for the safety of patients. Ners students because of its lack clinical experiences are at risk to make an error in medication or procedure to the patient. The purposes of this study are to identify types and causes error events conducted by ners students.Method: This is a qualitative study. The participants are 29 students for answering the open questionnaire and 5 students for in-depth interview. The instruments are open questionnaire and interview guideline. Data analysis is used content analysis.Result: This study revealed that the error is classiﬁed into 2 types: error related to medication and nursing procedures. The natures of error are from mild to severe error. The factors of error are classiﬁed into 3 categories: student factor, environment and preceptor factor. The student factors: lack of conﬁdence, nervous, ﬁrst time experience, and lack of practice. Environment factor: lack of facilities, emergency condition, lack of supervision, and lack of patient safety habit in the hospital. Preceptor factors: lack of guidance, unclear instruction.Discussion:The students feeling when doing an error is classiﬁed into 2: negative and positive feeling. Negative feelings are fear, feeling guilty. Positive feeling: motivated to learn. The student actions after doing an error are keep silent, inform to other students, or inform the preceptor or hospital nurses. The suggestion from this research is improving the skills lab education during academic phase and developing procedure for manage and prevent the error.